1985
DOI: 10.1177/030098588502200210
|View full text |Cite
|
Sign up to set email alerts
|

Dysentery Caused by Escherichia coli (S102-9) in Calves: Natural and Experimental Disease

Abstract: A dysentery syndrome was recognized among the Institute's calves at 18 to 21 days of age. It was reproduced experimentally in gnotobiotic calves with an atypical Escherichia coli (S102-9) isolated from the affected calves. In both natural and experimental disease the calves passed copious bright red blood in the feces and developed diarrhea. Walls of the colon and rectum were thickened, and the mucosa was reddened and covered by an exudate that contained mucus and blood clots. Bacteria were seen closely adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
55
0
2

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 20 publications
9
55
0
2
Order By: Relevance
“…Confocal microscopy of midileal mucosa from PMK5-inoculated loops revealed small foci of bacteria on the intestinal epithelium, similar to those detected by immunohistochemical staining of ileal mucosa from E. coli O157:H7-infected neonatal calves (8) and O157:H7-infected ileal loop mucosa (data not shown). These data, combined with observations that STEC colonizes the bovine small intestine in vivo (7,8,29) and can induce A/E-lesion formation on bovine distal ileum both in vivo and in vitro (7,8,47), indicate that the ligated ileal loop assay is physiologically relevant and can be used to dissect bacterial and host factors influencing enteropathogenic responses. The absence of enteropathogenic responses to E. coli O157:H7 may be explained by the age-related susceptibility of calves to these bacteria (5,8).…”
Section: Vol 70 2002 Enteropathogenic Responses To Stec In Cattle 949mentioning
confidence: 70%
See 1 more Smart Citation
“…Confocal microscopy of midileal mucosa from PMK5-inoculated loops revealed small foci of bacteria on the intestinal epithelium, similar to those detected by immunohistochemical staining of ileal mucosa from E. coli O157:H7-infected neonatal calves (8) and O157:H7-infected ileal loop mucosa (data not shown). These data, combined with observations that STEC colonizes the bovine small intestine in vivo (7,8,29) and can induce A/E-lesion formation on bovine distal ileum both in vivo and in vitro (7,8,47), indicate that the ligated ileal loop assay is physiologically relevant and can be used to dissect bacterial and host factors influencing enteropathogenic responses. The absence of enteropathogenic responses to E. coli O157:H7 may be explained by the age-related susceptibility of calves to these bacteria (5,8).…”
Section: Vol 70 2002 Enteropathogenic Responses To Stec In Cattle 949mentioning
confidence: 70%
“…Severe cases of infection of susceptible calves with bovine virulent STEC strains may result in atrophy of the villi, epithelial cell damage, diffuse infiltration of neutrophils into the lamina propria and intestinal lumen, and the formation of a pseudomembrane containing blood, fibrin, cellular debris, and neutrophils (29,46). A similar histopathology occurs in some cases of STECassociated hemorrhagic colitis in humans (27,55).…”
mentioning
confidence: 96%
“…A previous study in Sri Lanka had noted an association between V'TEC and calf diarrhoea [9]. Hall and co-workers [36] reported dysentery in calves associated with E. coli (strain S102-9) found to be serogroup 0 5 was not seen in the course of the present study or in a previous study of VTEC( serotypes in Sri Lanka [31], although it has been found at low prevalence in cattle faecal specimens [25] and retail meat products from North America [39]. Of V'TEC 0 serogroups previously found in Sri Lanka [31], 0 86, 0 128, 0 84, 0 103, 0 111, and 0 153 have been associated with human diseases [7,.…”
Section: Discussionmentioning
confidence: 99%
“…This lesion is associated with the accumulation of polymerised actin ®laments underneath the adhering bacteria, leading to the formation of a pedestal-like structure (Finlay et al, 1992;Knutton, 1994). AEEC strains have been implicated in diarrhoea and dysentery in human and animals including 2±8-week-old calves (Chanter et al, 1984;Hall et al, 1985;Donnenberg and Kaper, 1992;Mainil et al, 1993;China et al, 1998).…”
Section: Introductionmentioning
confidence: 99%